Pendampingan Branding serta Promosi Offline dan Digital UMKM Desa - Mohamad Ma'mun; M. Malfin Zainal Asyiqin Malfin; Rizka Rahma Wati Rahma; Trisfirdaona Rashamida Iqdam Ona; Andri Wicaksono Andri (LP3M IAIFA Kediri, 2025)
Empowering Micro, Small, and Medium Enterprises (MSMEs) is a strategic step in sustainably improving the village economy. This article discusses a training program titled